P435 Evaluation of remote triazole capillary blood testing to facilitate remote therapeutic drug monitoring (TDM): A validation study. (20th September 2022) - Nwankwo, Lisa; Donovan, Jackie; Ni, Melody; Loebinger, Michael; Armstrong-James, Darius; Shah, Anand
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Background: The advent of COVID-19 has meant that patients with chronic diseases needed to shield, however, investigations were needed to guide continual management of their disease. Remote monitoring options were evaluated to ensure the standard of care is not compromised. Purpose and Hypothesis: The aim was to validate remote (return-posted) capillary triazole blood testing and evaluate the potential role of remote TDM in chronic antifungal therapy. Materials and Methods: A single-center prospective cross-sectional study of remote finger prick capillary blood testing compared with gold standard venesection was performed. Remote finger prick capillary blood testing was validated compared to local standard venesection using comparative statistical analysis Comparative statistical analysis: Paired t-test, correlation and Bland-Altman were used to determine if there was agreement or association between the sampling methods. Results: A total of 66 patients receiving triazole therapy were recruited and 57 pooled pairs of remote capillary and venous triazole concentrations and metabolites were prospectively analyzed, with the rest of the blood samples not being analyzed due to insufficient sample, hemolysis, or undetectable triazole level of <0.2 mg/l. There was a significant difference in the comparison of the two methods of sampling with paired t -test at P <.0001. Bland-Altman analysis yielded wide bias (−49.07%) and wide limits of agreement (−85.5% to −12.64%). On average capillary triazole, concentrations were 37% lower than venous concentrations (Fig. 1). There was however a very strong correlation between capillary and venous tests (Pearson's correlation coefficient r = 0.9219, P <.0001, Fig. 2). Conclusions: Remote capillary triazole sampling does not appear interchangeable with venous sampling, but being strongly correlated and on average 2/3rd of the venous value, could be a predictor of venous triazole level, or be useful for intra-patient longitudinal monitoring. When incorporated into an outpatient clinical pathway it can improve shared decision-making and patient experience. Further research is required to determine appropriate target reference ranges if the new lower capillary levels can be used routinely, especially in the climate of COVID-19 where social distancing measures limit patient access to hospitals and clinics for routine investigations.